Scientific Substantiation of the Technology of Finely-Dispersed Metallurgical Sludge Bioconversion - S.D, Polischuk; A.A, Nazarova; D.G, Churilov; G.K., Rembalovich; M.Yu, Kostenko; I.S, Arapov (International Journal of Engineering and Technology, 2018)
In the course of human activities large quantities of industrial wastes, unused by-products, remnants of raw materials, materials that completely or partially change their properties, accumulate in nature. On the other hand, one of the important problems is the remediation and increase in the yield of agricultural land, especially in central Russia. Numerous data on the use of sludge sediments in the United States and Europe in growing agricultural crops have given grounds for assuming that such wastes can be used in Russian agriculture. The aim of the research work is experimental confirmation in field conditions the effectiveness of using metallurgical sludge accumulations for the remediation of soil resources in agriculture and increasing the yield of agricultural crops, especially in central Russia. The conducted research allowed to make a conclusion about the effectiveness of metallurgical sludge as a potential component of agricultural fertilizers. As test crops, technical plants,sunflower and rape, were selected as objects suitable for the bioconversion of metallurgical sludge. Crops treatment with 10 % solution of sludge turned to be the most effective means. It resulted in the increase of the sunflower field germination by 7 %, plant weight by 27.7-33.4 %, plant height by 33.9 % and leaf area by 11.6 % compared to the control. Parameters of the vegetative and generative functions of rapeseed plants changed as follows: field germination increased by 4 %, plant height by 13.8-33.6 %, plant weight by 20.0-25.5 % and photosynthesis productivity by 33.7 %. Thus, metallurgical sludge can be considered as an effective stimulator of vegetative and generative functions of agricultural crops in relation to these soil and climatic conditions. The obtained biochemical and electron microscopic data convincingly indicate the possibility of including the components of the sludge in the physiological processes of plants, including as trace elements, which is the reason for the observed stimulation of plants growth and development.Â Â